2017
DOI: 10.1017/s0033291716003408
|View full text |Cite
|
Sign up to set email alerts
|

Childhood interleukin-6, C-reactive protein and atopic disorders as risk factors for hypomanic symptoms in young adulthood: a longitudinal birth cohort study

Abstract: Background. There are no existing longitudinal studies of inflammatory markers and atopic disorders in childhood and risk of hypomanic symptoms in adulthood. This study examined if childhood: (1) serum interleukin-6 (IL-6) and C-reactive protein (CRP); and (2) asthma and/or eczema are associated with features of hypomania in young adulthood.Method. Participants in the Avon Longitudinal Study of Parents and Children, a prospective general population UK birth cohort, had non-fasting blood samples for IL-6 and CR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
14
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 52 publications
0
14
1
Order By: Relevance
“…However, in the other study (n = 60) this relationship was not found (30). There is slight evidence that atopic eczema is associated with low grade inflammation: Young psychiatric patients with atopic eczema showed higher levels of inflammatory markers compared with those without eczema (16,18). To the best of our knowledge, the association between atopic eczema and low grade inflammation, has not been previously demonstrated in an unselected adult population.…”
Section: Discussionmentioning
confidence: 77%
See 1 more Smart Citation
“…However, in the other study (n = 60) this relationship was not found (30). There is slight evidence that atopic eczema is associated with low grade inflammation: Young psychiatric patients with atopic eczema showed higher levels of inflammatory markers compared with those without eczema (16,18). To the best of our knowledge, the association between atopic eczema and low grade inflammation, has not been previously demonstrated in an unselected adult population.…”
Section: Discussionmentioning
confidence: 77%
“…Studies with limited sample size have showed that low grade inflammation is also present in chronic urticaria (n = 58) (13), lichen ruber planus (n = 55) (14) and rosacea (n = 60) (15). Recent studies have demonstrated that children and young adults with atopic eczema or allergic sensitization have elevated CRP levels (16)(17)(18). In contrast, no association has been found between acne vulgaris and elevated CRP (12).…”
mentioning
confidence: 99%
“…Another study also showed sIL-6 R level reflecting the illness activity in bipolar disorder [41]. In a 13-year longitudinal study, higher levels of systemic inflammatory marker IL-6 in childhood were associated with hypomanic symptoms in young adulthood [42]. Higher sIL-6R levels were also associated with lower functional connectivity between the medial prefrontal cortex (mPFC) and subcortical structures involved in emotional processing in BD patients [43].…”
Section: Discussionmentioning
confidence: 94%
“…This is in agreement with earlier reports. 1,3,[15][16][17][18][19][20] It is clear from the results that elevated CRP and IL-6 are seen in DN patients having multiple cutaneous complications proving that a rise in inflammatory marker levels is directly related to cutaneous complications (Table 5).…”
Section: Discussionmentioning
confidence: 98%
“…15 Inflammation can be assessed by an elevation in inflammatory markers specifically CRP and IL-6. 16,17 Inflammation been defined as a complex physiological response to harmful stimulation of the body followed by clinical symptoms like redness, swelling, heat and pain. It is also characterized by elevated levels of inflammatory markers of which CRP and IL-6 are significant and most commonly employed in clinical assessment of inflammation.…”
Section: Discussionmentioning
confidence: 99%